Combating COVID-19 with tissue engineering: a review - GÜNDÜZ, OĞUZHAN (SPRINGERNATURE, 2021)
The ongoing COVID-19 pandemic triggered by SARS-CoV-2 emerged from Wuhan, China, firstly in December 2019, as well spread to almost all around the world rapidly. The main reason why this disease spreads so many people in a short time is that the virus could be transmitted from an infected person to another by infected droplets. The new emergence of diseases usually may affect multiple organs

moreover, this disease is such an example. Numerous reported studies focus on acute or chronic organ damage caused by the virus. At this point, tissue engineering (TE) strategies can be used to treat the damages with its interdisciplinary approaches. Tissue engineers could design drug delivery systems, scaffolds, and especially biomaterials for the damaged tissue and organs. In this review, brief information about SARS-CoV-2, COVID-19, and epidemiology of the disease will be given at first. After that, the symptoms, the tissue damages in specific organs, and cytokine effect caused by COVID-19 will be described in detail. Finally, it will be attempted to summarize and suggest the appropriate treatments with suitable biomaterials for the damages via TE approaches. The aim of this review is to serve as a summary of currently available tissue damage treatments after COVID-19.
Keywords: COVID-19; SARS-CoV-2; Tissue engineering; Regenerative medicine; Organ; MESENCHYMAL STEM-CELLS; SMALL-INTESTINAL SUBMUCOSA; CONVERTING ENZYME 2; REGENERATIVE MEDICINE; CYTOKINE STORM; LIVER-INJURY; NERVE DEFECT; CORONAVIRUS; SCAFFOLDS; GRAFT